Existence of brain 5-HT1A-5-HT2A isoreceptor complexes with antagonistic allosteric receptor-receptor interactions regulating 5-HT1A receptor recognition - Borroto Escuela, Dasiel Óscar; Li, Xiang; Tarakanov, Alexander O.; Savelli, David; Narváez-Peláez, Manuel; Shumilov, Kirill; Andrade-Talavera, Yuniesky; Jiménez-Beristain, Antonio; Pomierny, Bartosz; Díaz-Cabiale, Zaida; Cuppini, Riccardo; Ambrogini, Patrizia; et al. (American Chemical Society, 2017)
Studies on serotonin-selective reuptake inhibitors have established that disturbances in the ascending 5-HT neuron systems and their 5-HT receptor subtypes and collateral networks to the forebrain contribute to the etiology of major depression and are targets for treatment. The therapeutic action of serotoninselective reuptake inhibitors is of proven effectiveness, but the mechanisms underlying their effect are still unclear. There are many 5-HT subtypes involved; some need to be blocked (e.g., 5-HT2A, 5-HT3, and 5-HT7), whereas others need to be activated (e.g., postjunctional 5-HT1A and 5-HT4). These state-of-the-art developments are in line with the hypothesis that the development of major depression can involve an imbalance of the activity between different types of 5-HT isoreceptors. In the current study, using in situ proximity ligation assay (PLA), we report evidence for the existence of brain 5-HT1A-5-HT2A isoreceptor complexes validated in cellular models with bioluminescence resonance energy transfer (BRET2) assay. A high density of PLA-positive clusters visualizing 5-HT1A- 5-HT2A isoreceptor complexes was demonstrated in the pyramidal cell layer of the CA1-CA3 regions of the dorsal hippocampus. A marked reduction in the density of PLA-positive clusters was observed in the CA1 and CA2 regions 24 h after a forced swim test session, indicating the dynamics of this 5-HT isoreceptor complex. Using a bioinformatic approach, previous work indicates that receptors forming heterodimers demonstrate triplet amino acid homologies. The receptor interface of the 5-HT1A-5-HT2A isoreceptor dimer was shown to contain the LLG and QNA protriplets in the transmembrane and intracellular domain, respectively. The 5-HT2A agonist TCB2 markedly reduced the affinity of the 5-HT1A agonist ipsapirone for the 5-HT1A agonist binding sites in the frontal lobe using the 5-HT1A radioligand binding assay. This action was blocked by the 5-HT2A antagonist ketanserin. It is proposed that the demonstrated 5- HT1A-5-HT2A isoreceptor complexes may play a role in depression through integration of 5-HT recognition, signaling and trafficking in the plasma membrane in two major 5-HT receptor subtypes known to be involved in depression. Antagonistic allosteric receptor-receptor interactions appear to be involved in this integrative process.
Keywords: Depresión; Serotonina - Receptores; Proteínas G; Serotonin 5-HT1A receptor; Serotonin 5-HT2A receptor; Isoreceptor complexes; Oligomerization; G protein-coupled receptors; Allosteric modulation; Receptor–receptor Interactions; Depression